2007
DOI: 10.1197/j.aem.2006.09.048
|View full text |Cite
|
Sign up to set email alerts
|

Need for Standardized Sign‐out in the Emergency Department: A Survey of Emergency Medicine Residency and Pediatric Emergency Medicine Fellowship Program Directors

Abstract: There is wide variation in the sign-out processes followed by different EDs. A majority of those surveyed expressed the need for standardized sign-out systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…Previous literature has revealed that few trainees receive formal training in effective hand-off communication 2,12 despite the ubiquitous nature of this task performed by interns in every specialty. The lack of trainee preparation on how to perform hand-offs impacts a number of stakeholders, including residency program directors 13 .…”
Section: Aimmentioning
confidence: 99%
“…Previous literature has revealed that few trainees receive formal training in effective hand-off communication 2,12 despite the ubiquitous nature of this task performed by interns in every specialty. The lack of trainee preparation on how to perform hand-offs impacts a number of stakeholders, including residency program directors 13 .…”
Section: Aimmentioning
confidence: 99%
“…3,[6][7][8] Yet, the process of teaching physician handoffs between specialties is not well described in the emergency medicine (EM) literature. 6,[9][10][11][12] No best practice recommendations exist and there is no universally taught, standardized handoff format that emergency physicians use for patient care. 10 Situation-Background-Assessment-Recommendation (SBAR) provides a framework for effective communication among members of the health care team.…”
Section: Introductionmentioning
confidence: 99%
“…73 A survey of emergency residency programs revealed that 75% had no formal didactic training and 90% had no written policy about ToCs. 9 Numerous organizations, including The Joint Commission 74 76 The ACGME, a professional organization responsible for the accreditation of numerous residency education programs, requires specific attention to ToC procedures in both residency and fellowship training programs, creating common standards for all training programs. 77 The American Association of Colleges of Nursing also includes knowledge of and ability to perform appropriate ToC practices as a competency for graduate nursing.…”
Section: Teaching Tocsmentioning
confidence: 99%
“…8 In addition to the need for more evidence gathering, surveys of graduate medical education program directors have concluded that there is a perceived need for emergency medicine and pediatric emergency medicine training programs to provide specific guidance to trainees regarding ToC processes. 9 A new clinical report from the …”
Section: Introductionmentioning
confidence: 99%